2005
DOI: 10.1080/10715760500072156
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized low density lipoprotein, autoantibodies against them and homocysteine serum levels in diagnosis and estimation of severity of coronary artery disease

Abstract: The oxidative hypothesis of atherosclerosis proposes that oxidative modification of low density lipoprotein (LDL) plays a critical role in atherogenesis. The evaluation of LDL oxidation in vivo is therefore very important. However, data concerning the evaluation of the above biochemical marker is very limited in clinical practice. This study was conducted to test the hypothesis that plasma levels of ox-LDL reflect atherosclerosis and determine the clinical significance in the measurement of circulating ox-LDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
1
24
0
5
Order By: Relevance
“…multiple AMI, for example), only the first one was taken into account in the survival analysis. A total of 15 fatal (9 AMI and 6 strokes) and 52 non-fatal events (20 AMI,15 strokes, 11 TIA and 6 AF) were registered during follow-up.…”
Section: Definition Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple AMI, for example), only the first one was taken into account in the survival analysis. A total of 15 fatal (9 AMI and 6 strokes) and 52 non-fatal events (20 AMI,15 strokes, 11 TIA and 6 AF) were registered during follow-up.…”
Section: Definition Of Outcomesmentioning
confidence: 99%
“…[9][10][11] Several studies have demonstrated increased titers of antibodies recognizing oxLDL in patients with coronary, 12 cerebral 13 or peripheral artery disease, 14 suggesting that they can serve as markers of the atherosclerotic process. 13,[15][16][17] However, whether these autoimmune responses have protective or pathogenetic effects remains to be fully elucidated. In the present study we investigated if autoantibodies against p210 at the time of carotid endarterectomy (CEA) predict risk for future cardiovascular (CV) events.…”
mentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the accelerated atherosclerotic changes seen with glucose intolerance, and this includes inflammation [6,7], increased platelet activation [8,9], and oxidative stress [10]. After the initial studies by Goldstein et al [11] on modification of low-density lipoprotein (LDL) and its role in atherosclerosis, several studies have investigated the role of modified LDL as a biochemical risk factor for atherosclerosis [12][13][14][15]. Of the various modified forms of LDL, oxidized LDL (OX-LDL) has gained a lot of interest recently [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Oxidized LDL (oxLDL) accumulates within the intramural extracellular matrix of the coronary and carotid vasculature, where it binds to macrophages (Feng et al 2010). Oxidative modification of LDL produces reactive aldehydes, phospholipids, and lipid peroxidation products such as malondialdehyde-modified LDL (MDA-LDL), a representative form of oxLDL in which oxidation occurs mainly among the free lysine amino groups of apolipoprotein B. OxLDL levels in vivo, both in plasma and in atheromatous plaques, are strongly associated with coronary artery disease progression, the vulnerability of atherosclerotic lesions to rupture, and the severity of the clinical presentation (Nishi et al 2002;Faviou et al 2005;Hiki et al 2009). Scavenger receptors on macrophages interact with oxLDL, leading to the formation of macrophage foam cells and fatty streaks, and the progression of atherosclerotic plaques (Jeon et al 2007;Osto et al 2008).…”
Section: Introductionmentioning
confidence: 99%